Metacarpal Acupressure Reduced Pain in the First Stage of Labor - Rejeki, Sri; Hartiti, Tri; Sulichan, Achmad; Machmudah, Machmudah (University of Muhammadiyah Semarang, 2019)
Pain during labor will cause psychological disorders for mothers, such as 87% of postpartum blues, 10% of depression and 3% of psychosis. Therefore, intervention to relieve pain level is necessary to prevent complications for mother and fetus during the process and after delivery. One of the simple methods to relieve the pain level of childbirth is metacarpal acupressure. The application of this method is usually only done by health workers, although a spouse or other family member can conduct it. This study aimed to describe the application of metacarpal acupressure by the husband to relieve pain level in first delivery women. The study used a descriptive-analytic design. The population was 40 husbands, who were waiting for their wives at the first stage of labor. The husbands have been trained about Acupressure methods. The sampling method used a consecutive sampling method. The results of the study revealed 75% of husbands did well for practicing acupressure methods, 60% of women claimed they got pain relief after given Acupressure by their husband. The recommendation of this study is the importance of a spouse's presence in first stage labor for reducing the pain of mothers in childbirth.